[Professor Etsuko Bannai lectures on "Four-weight spin models constructed from certain type II matrices"] - Bannai, Etsuko (Animo Repository, 1998)
Professor Etsuko Bannai, a faculty of Kyushuu University, Fukuoka, Japan, lectured on Four-weight spin models constructed from certain type II matrices. Bannai's main field of interest is algebraic combinatorics.